VIDEO EDUKASI MENINGKATKAN PENGETAHUAN PERAWAT TENTANG KOMUNIKASI TERAPEUTIK DI RUMAH SAKIT - Intan Pratiwi, Luh Yudita; Darma Yanti, Ni Putu Emy; Rahajeng, Indah Mei (Coping: Community of Publishing in Nursing, 2022)
Therapeutic communication is one of the components that nurses need to pay attention to when providing health services. Quality of therapeutic communication implementation may be influenced by several factors, including nurses’ knowledge. Knowledge can be obtained from several ways, which one education videos. This study aims to determine the effect of providing educational videos on the level of knowledge of nurses about therapeutic communication in the General Hospital of Buleleng. The type used in this research is correlational analytic research design, one group pre-test post-test design, proportional sampling technique stratified random sampling with total sample of 45 nurses. The results obtained this study before being given the educational video most of respondents had sufficient knowledge, after being given the video most the respondent showed had good knowledge. The results of the Wilcoxon test obtained a p value of 0,000 (<0,05) which means that the custom of giving educational videos on the level of knowledge of nurses about therapeutic communication at the General Hospital of Buleleng. Educational videos are one of the effective and efficient learning media in disseminating information.